Pengembangan Pemeberdayaan Masyarakat Berbasis Potensi Lokal (Limbah Tekstil dari Pabrik) di Kecamatan Rancasari Kota Bandung - Fachruroji Fachruroji; Lilis Irmawatie (LPPM UNINUS, 2015)
Community empowerment in Rancasari focuses on two villages, namely Cipamokolan and Mekarjaya. This empowerment is intended to give bit of capital for community member in both villages in order to improve their skills by giving the training in making door-mats. By this training, the community is expected to acquire skills, be able to do something useful, and earn extra income. The method used is a community empowerment refers to the concept of